Groundwater flow and solute transport in fracture zones: an improved model for a large-scale field experiment at Äspö (Sweden) - Molinero, Jorge; Samper, Javier (Journal of hydraulic research, 2004)
157-172 Groundwater flow and solute transport in fracture zones: an improved model for a large-scale field experiment at Äspö (Sweden) Jorge Molinero E.T.S. Ingenieros de Caminos Canales y Puertos, Campus de Elvina Universidadde A Coruña 15192 A Coruña Spain E-mail: molinero@iccp.udc.es Javier Samper E.T.S. Ingenieros de Caminos Canales y Puertos, Campus de Elvina Universidad de A Coruna, 15192 A Coruna, Spain. E-mail: jsc@iccp.udc.es Several countries around the world are considering the final disposal of high-level radioactive waste in deep repositories located in fractured granite formations. Evaluating the long term safety of such repositories requires sound conceptual and numerical models of groundwater flow, solute transport and chemical and radiological processes. These models are being developed from data and knowledge gained from in situ experiments carried out at deep underground laboratories such as that of Äspö, Sweden, constructed in fractured granite. The Redox Zone Experiment is one of such experiments performed at Aspö in order to evaluate the effects of the construction of the access tunnel on the hydrogeological and hydrochemical conditions of a fracture zone intersected by the tunnel. Hydrochemical and isotopic data of this experiment were interpreted by Banwart et al. (Appl. Geochem., 14, 1999, 873) using a mass-balance approach based on a qualitative description of groundwater flow conditions. Such an interpretation, however, is subject to uncertainties related to an oversimplified conceptualization of groundwater flow. Here we present finite element numerical models of groundwater flow and solute transport for this fracture zone. The first model is based on Banwart's conceptual model. It presents noticeable inconsistencies and fails to match simultaneously observed drawdowns and chloride breakthrough curves. To overcome its limitations, a revised flow and transport model is presented which relies directly on available hydrodynamic and transport parameters, is based on the identification of appropriate flow and transport boundary conditions and uses, when needed, solute data extrapolated from nearby fracture zones. A significant quantitative improvement is achieved with the revised model because its results match simultaneously drawdown and chloride data. Other improvements are qualitative and include: ensuring consistency of hydrodynamic and hydrochemical data and avoiding inconsistencies in the hydrodynamic model. These results enable us to conclude that quantitative analyses of hydrochemical data should rely on sound conceptual and numerical flow and transport models which provide an appropriate framework for checking the consistency of hydrodynamic and hydrochemical data. This framework can be subsequently used for coupling groundwater flow, solute transport and chemical processes in the future.